Legal Conflicts in the Border Dispute between Indonesia and Timor Leste - Rato, Dominikus (University of Jember, 2019)
This study aims to find the pattern of dependable approach in the border dispute settlement between Indonesia and Timor Leste in Oecusse. Historically, the community lived in the border area came from one ancestor. Because of social-political problems, however, the community subsequently followed the trajectory for which the partition between Indonesia and Timor Leste was undeniable. As a result of the partition, in the context, adat land should become the collective right of the community, which is situated under one adat law system but in the different national jurisdictions. This study questions on what causes collective land conflicts at the border of these countries. Using socio-legal and local wisdom approaches, as it is subsequently analyzed according to adat law, the study finds the cause that emerged as the result of the legal conflict between adat law and state law. If the state hands over the problem to adat communities or traditional leaders, based on their adat law dispute resolution, the conflict will resolve quickly. This study recommends the two states, Indonesia and Timor Leste, to provide the dispute resolution to adat or traditional leaders based on their adat law. Keywords: Legal Conflicts, Border Dispute, Adat Law.